Optimization and comparison of argon plasma-induced quantum well intermixing using RIE and ICP - Leong, Daniel Woon Loong. (2008)
In this project, a novel quantum well intermixing (QWI) technique using inductively-coupled (ICP) and reactive-ion etcher (RIE) Argon plasma exposure has been developed.